Kitsch as Experience of the World - Darío Hernández Guerra (ESPES)
The term ‘kitsch’, widely laden with negative connotations, has often been used to designate worthless art, synonymous with artistic failure. However, there is something in kitsch that, beyond its apparent poor quality, distinguishes it from other art forms as something novel, peculiar, and even profoundly interesting. Kitsch art generates an irresistible force of attraction towards its spectators that greatly captures attention. This allure belongs to a rarefied nature that brings to light the pleasures and delight of purely aesthetic appeal. Its apparent lack of value is thus mitigated by its promotion of a radically relativistic attitude that establishes a conciliatory balance between attractiveness and horridness. It is here that all its power to shape our experience of the world resides.